Peran Pemasaran dan Inovasi Digital melalui QRIS dalam Mendorong Pertumbuhan UMKM: Studi Kasus di 15A Iringmulyo, Metro Timur - Dini Endang Puspita; Nur Syamsiyah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The development of the MSME sector plays an important role in driving national economic growth. Marketing and utilization of QRIS technology are factors that can increase business development, especially amidst tight competition and low adoption of digital payment systems. This study aims to determine the effect of marketing and utilization of QRIS technology on the development of the MSME sector. The research method used is quantitative with a population of MSMEs in the culinary sector in 15A Iringmulyo Metro Timur. The sample consisted of 50 respondents, determined through the Slovin formula with the Simple Random Sampling technique. The results of the study showed that partially, marketing has a positive and significant effect on the development of the MSME sector, the utilization of QRIS technology has a positive and significant effect on the development of the MSME sector. Simultaneously, both variables have a positive and significant effect on the development of the MSME sector. These findings indicate that optimizing marketing strategies and utilizing digital payment systems are important factors in supporting the sustainability and growth of micro, small, and medium enterprises in the area.